Juvenile justice in global perspective - Zimring, Franklin E.; Langer, Máximo; Tanenhaus, David Spinoza (Youth, crime, and justice series, 2015)
Among developed nations, the US has one of the most extreme and harsh criminal justice systems in the world - there is overwhelmingly more violence, more punishment, and more incarceration for both adults and juveniles here. But while American scholars may have extensive knowledge about other justice systems around the world and how adults are treated, juvenile justice systems and the plight of youth who break the law throughout the world is less often studied. This volume fills a large gap in the study of juvenile justice by providing an unprecedented comparison of criminal justice and juvenile justice systems across the world, looking for points of comparison and policy variance that can lead to positive change in the United States